ДОСВІД ПРОЄКТУВАННЯ МАЛОРОЗМІРНИХ ГАЗОТУРБІННИХ ДВИГУНІВ ДЛЯ БЕЗПІЛОТНИХ ЛІТАЛЬНИХ АПАРАТІВ - KATRENKO, M. O.; STRELNIKOV, H. O.; PRYADKO, N. S. (текст 3, 2025)
DOI: https://doi.org/10.15407/itm2025.02.035 This paper is concerned with low-thrust air-feed jet engines, which are used in unmanned and manned aerial vehicles, power plants, etc. The paper presents an overview of existing aerial vehicles that use low-thrust air-feed jet engines of various types. Consideration is given to the basic construction and schematic diagrams of gas-turbine engines of thrust 100 to 3,000 N.  Experience in the design, making, and operation of air-feed jet engines as a part of unmanned aerial vehicles for various purposes is overviewed. The features of existing low-thrust engines are identified. It is shown that parametric data on low-thrust air-feed jet engines should be refined, supplemented, and collated with their unification in mind.  The thrust and specific performance characteristics of currently available engines and the trends in their refinement are presented. The correctness of the methodological approaches to this study is verified by comparison with other authors’ results. The goal of this study is to identify the main lines of design and making of low-thrust air-feed jet engines for unmanned aerial vehicles and the trends in their refinement and use. The novelty of this study lies in obtaining new data on the effect of the unmanned aerial vehicle parameters, purpose, and flight conditions on the choice of the low-thrust gas-turbine engine type, component units, and key characteristics. The obtained results allow one to identify the range of the work process parameters of engines in specifying the requirements for and the design of the main units and the engine as a whole. The practical significance of the results lies in the possibility of using the obtained data in designing small-size gas-turbine engines for unmanned aerial vehicles and in refining computational procedures. REFERENCES 1. Khalatov A. A., Nemchin O. F., Shkvar Ye. O. Kuzmin A. V., Kobzar S. H. Combat Small-Size Jet Unmanned Aerial Vehicles. Dnipro: Lira, 2023. 144 pp. (In Ukrainian). 2. Handbook of Unmanned Aerial Vehicles. Valavanis K. P., Vachtsevanos G. J. (Eds.). Dordrecht, Netherlands: Springer Netherlands, 2015. 3022 pp. URL: https://dh8.kr/workshop/sejong_control/Handbook_of_Unmanned_Aerial_Vehicles.pdf (Last accessed on March 10, 2025). 3. Arjomandi M. Classification of Unmanned Aerial Vehicles. Adelaide, Australia: University of Adelaide, 2007. 49 pp. URL: https://www.academia.edu/2055673/Classification_of_Unmanned_Aerial_Vehicles (Last accessed on March 10, 2025). 4. Classification of the Unmanned Aerial Systems | GEOG 892: Unmanned Aerial Systems. URL: https://www.e-education.psu.edu/geog892/node/5 (Last accessed on March 10, 2025). 5. Oktay T., Coban S. A review of tactical unmanned aerial vehicle design studies. The Eurasia Proceedings of Science, Technology, Engineering & Mathematics (EPSTEM). Antalya, Turkey: ISRES Publishing, 2017. V. 1. Pp. 30-35. URL: http://www.epstem.net/tr/download/article-file/361494 (Last accessed on March 10, 2025). 6. Coban S., Oktay T. Unmanned aerial vehicles (UAVs) according to engine type. J. Aviat. 2018. URL: https://dergipark.org.tr/tr/download/article-file/598807 (Last accessed on March 10, 2025).https://doi.org/10.30518/jav.461116 7. Chin W.J., Sern V.C.Y. Unmanned aerial vehicle: Development trends & technology forecast // DSTA Horizons. 2005. V. 1. Pp. 20-37. URL: https://www.researchgate.net/publication/293115444_Unmanned_aerial_vehicle_Development_trends_technology_in_Singapore (Last accessed on March 10, 2025). 8. Zhang B. et al. Overview of propulsion systems for unmanned aerial vehicles. Energies. 2022. V. 15. No. 2. 455.https://doi.org/10.3390/en15020455 9. Brelje B.J., Martins J.R.R.A. Electric, hybrid, and turboelectric fixed-wing aircraft: A review of concepts, models, and design approaches // Prog. Aerosp. Sci. 2019. V. 104. Pp. 1-19.https://doi.org/10.1016/j.paerosci.2018.06.004 10. Hassanalian M., Abdelkefi A. Classifications, applications, and design challenges of drones: A review // Prog. Aerosp. Sci. 2017. V. 91. Pp. 99-131.https://doi.org/10.1016/j.paerosci.2017.04.003 11. Lidor A., Weihs D., Sher E. Novel propulsion systems for micro aerial vehicles. J. Propuls. Power. 2019. V. 35. No. 1. Pp. 243-267.https://doi.org/10.2514/1.B36930 12. Birch G.C., Griffin J.C., Erdman M.K. UAS Detection, Classification, and Neutralization: Market Survey 2015. SAND2015-6365. Livermore, CA, US: Sandia National Laboratories, 2015. P. 74.https://doi.org/10.2172/1222445 13. Theory and Design of Air-Feed Jet Engines, S. M. Shlyakhtenko (Ed.). Moscow: Mashinostroyeniye, 1987. 568 pp. (In Russian). 14. Dutczak J. Micro turbine engines for drones propulsion. IOP Conf. Ser. Mater. Sci. Eng. 2016. V. 148. No. 1. 012063.https://doi.org/10.1088/1757-899X/148/1/012063 15. Herasimenko V. P. Aircraft Engine Theory. Kharkiv: Kharkiv National Aerospace University "Kharkiv Aviation Institute", 2003. 199 pp. (In Ukrainian). 16. Jet Central: miniature jet engines for the seriuos flyer. URL: https://jetcentral.com.mx/ (Last accessed on September 15, 2022). 17. Rostopchin V. V. Microturbojets for unmanned aerial vehicles. Bespilotnaya Aviatsiya. 2005. 15 pp. URL: https://www.researchgate.net/publication/348540913_Analiz_konstrukcii_i_ocenka_harakteristik_mikro-TRD (Last accessed on March 10, 2025). 18. Minijets.org. Jet engine from 0 to 100 Kg thrust Class. Minijets. URL: https://minijets.org/en/0-100 (Last accessed on March 10, 2025). 19. Sehra A. K., Shin J. Revolutionary Propulsion Systems for 21st Century Aviation: NAS 1.15:212615. Cleveland, Ohio, US: NASA Glenn Research Center, 2003. P. 13. URL: https://ntrs.nasa.gov/api/citations/20040001042/downloads/20040001042.pdf (Last accessed on October 7, 2003). 20. Ponomarev B. A. The Present and the Future of Aircraft Engines. Moscow: Voenizdat, 1982. 240 pp. (In Russian). 21. 1944-2000 Engines: Aircraft, Rocket, Marine, and Industrial Ones. Moscow: AKS-Konversalt, 2000. 464 pp. (In Russian). 22. Foreign Aircraft Engines: Handbook. L. I. Sorokin (Ed.). Moscow: Aviamir Publishing House, 2000. 534 pp. (In Russian). 23. Connors J. The engines of Pratt & Whitney: a technical history. Ned Allen (Ed.-in-Chief). American Institute of Aeronautics and Astronautics, Inc., 2010. 561 pp. URL: https://doi.org/10.2514/5.9781600867293.0000.0000 (Last accessed on October 7, 2023).https://doi.org/10.2514/5.9781600867293.0000.0000 24. Elodie Roux. Turbofan and Turbojet Engines: Database Handbook. Blagnac, France. 2007. 596 pp. URL: https://compress-pdf-free.obar.info/ (Last accessed on March 10, 2025). 25. Leyes R. A. II., Fleming W. A. The history of North American small gas turbine aircraft engines. American Institute of Aeronautics and Astronautics, Inc., Reston, Virginia. 1999. 998 pp. URL: https://www.semanticscholar.org/paper/The-History-of-North-American-Small-Gas-Turbine-Leyes-Fleming/ (Last accessed on October 7, 2003).https://doi.org/10.2514/4.473326 26. St.Peter J. The history of aircraft gas turbine engine development in the United States: a tradition of excellence. International Gas Turbine Institute of the American Society of Mechanical Engineers. Atlanta, Georgia. 1999. 592 pp. URL: https://apps.dtic.mil/sti/tr/pdf/ADA211347.pdf (Last accessed on March 10, 2025). 27. Sullivan K. H, Milberry L. Power. The Pratt and Whitney Canada Story. Toronto: CANAV Books, 1989. 320 pp. 28. Turbomeca 1938 - 1988. Cinquante annees de progres continus dans les turbo-machines. Bordes. Realisation Service Documention Turbomeca. 1989. 116 pp. URL: https://openlibrary.org/show-records/marc_loc_2016/BooksAll.2016.part30.utf8:127974393:801 (Last accessed on March 10, 2025). 29. Wilkinson P.H. Aircraft Engines of the World 1966/1967. International, Pan American and Universal. 304 pp. URL: https://raes.soutron.net/Portal/Default/en-GB/RecordView/Index/57630 (Last accessed on March 10, 2025).